The National SOM Survey 2005 - SOM Institute, University of Gothenburg (University of Gothenburg, 2007)
Since 1986 the SOM-institute has been carrying out an annual nation-wide survey of Swedish opinions. This is accordingly the twentieth survey in this series. The SOM-institute is a collaboration between three departments at Göteborg University: the Institute for Journalism and Mass Communication, the Department of Political Science, and the School of Public Administration. Since 1998 the survey includes two nation representative samples and uses two different mail questionnaires. One of the questionnaires mainly deals with questions on politics, economy and working life, while the other mainly deals with media, culture and health.
In 2005 approximately one fourth of the questions asked in the two questionnaires are common for both samples, for example questions about media habits, political attitudes, leisure activities, and social background. The questionnaire on politics include ten different subject fields: news and media; politics and society; the surrounding world; society and public service; crises awareness; environment and energy; knowledge and society; activities, interests, and values; work life; and background questions. The media questionnaire is divided into eleven subject fields: news and papers; politics and society; radio and television; possession of technical equipment, internet and other media; periodicals, books and libraries; movies; advertisment; media and society; activities, interests, and values; work life and background questions.

Purpose:

The main purpose is to establish time series that enable researchers to analyse how various changes in society affect people's attitudes and behaviour.

Detta är den tjugonde undersökningen i serien Riks-SOM, en nationell frågeundersökning med syfte att kartlägga den svenska allmänhetens vanor och attityder på temat samhälle, opinioner och medier.

Riks-SOM 2005 genomfördes som två undersökningar med två representativa urval och två olika formulär, där datainsamlingarna genomfördes parallellt och under identiska förhållanden. Frågeformulären skiljer sig något åt i det att tyngdpunkten i det ena formuläret ligger på politik och samhälle, medan det andra har en tonvikt på frågor om medier, kultur och livsstil. Ungefär en fjärdedel av frågorna är gemensamma för de båda frågeformulären och kan därmed analyseras med dubbla urvalsstorleken som grund.

Politikformuläret innehåller tio olika frågeområden: nyheter och medier; politik och samhälle; omvärldsfrågor; samhälle och service; krisberedskap; miljö och energi; kunskap och samhälle; aktiviteter, intressen och värderingar; arbetsliv; samt bakgrundsfrågor. Medieformuläret tar upp elva frågeområden: nyheter och tidningar; politik och samhälle; radio och TV; teknikinnehav, internet och andra medier; tidskrifter, böcker och bibliotek; film; reklam; medier och samhälle; aktiviteter, intressen och värderingar; arbetsliv; samt bakgrundsfrågor.

Syfte:

Huvudsyftet är att etablera tidsserier som gör det möjligt att analysera hur olika samhällsförändringar påverkar människors attityder och beteenden.
Den nationella SOM-undersökningen 2005
Riks-SOM 2005
Keywords: mass media; massmedia; population migration; migration; energy; energi; environment; miljö; mass media exposure; massmediaexponering; leisure time; fritid; european union; europeiska unionen; political interest; politiskt intresse; nuclear energy; kärnkraft; membership; medlemskap; cinema attendance; biobesök; party identification; partiidentifikation; trade union membership; medlemskap i fackförening; book use; bokanvändning; television channels; tv-kanaler; news; nyheter; journalism; journalistik; advertising; reklam; political allegiance; politisk anhängare; political participation; politiskt deltagande; television viewing; tv-tittande; research; forskning; religious affiliation; religiös tillhörighet; audio and video equipment; ljud- och videoutrustning; mobile communication; mobilkommunikation; internal politics; inrikespolitik; political parties; politiska partier; internet use; internetanvändning; cinema; bio; political leaders; politiska ledare; citizen participation; medborgardeltagande; clubs; föreningar; libraries; bibliotek; leisure time activities; fritidsaktiviteter; renewable energy; förnybar energi; radio listening; radiolyssnande; CORS; CORS; Media; Media; Environment and conservation; Miljö och naturvård; Political behaviour and attitudes; Politiska beteenden och attityder; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap